Demographic Transition and Healthcare Challenges in Nepal: A Focus on Magar Community (Shodhmala शोधमाला, 2026)
Nepal is going through a big demographic change that includes lower birth and death rates, an aging population, and changes in the age structure. All of these changes have big effects on economic growth and the growing need for healthcare. This change from high to low birth and death rates is caused by longer life expectancy, better literacy, and public health programs that are aimed at specific groups. But there are still big differences in health care and socio-economic status between marginalized ethnic groups in Nepal, especially the Magar minority, which makes up about 6.9 percent (1.9 million) of the country's population. Magar communities, which mostly live in rural highland areas, have trouble getting contemporary healthcare because they are isolated and there aren't many medical facilities nearby. This research used a mixed-methods approach, combining national demographic and health survey data with ethnographic fieldwork to investigate the connections between macro-level population changes and localized health practices. Findings show that people still rely on traditional healing methods and don't have easy access to expert medical care. To improve health outcomes in Nepal, it is important to strengthen rural health infrastructure, community-based healthcare programs, and combine traditional and allopathic systems.